(untitled) (Semiárida, 2025)
The increase in density, cover and distribution of woody species in the world´s natural grasslands is a cause for concern due to the negative impact on livestock production. Various strategies and technologies were developed to control woody plants, among them the most used are fire, mechanical work and application of herbicides. The objective of the work was to evaluate the damage caused by the application of different hormonal herbicides, at different hormonal herbicides, at different doses, on the woody species (ex Prosopis flexuosa var. flexuosa, Algarrobo), Neltuma flexuosa var. depressa (ex Prosopis flexuosa var. depressa, Alpataco), Condalia microphylla (piquillín) y Lycium chilense (llaollín) ant in the herbaceous stratum. Also, the total aerial herbaceous production (BHAT) and aerial biomass of perennial poaceae (BAPP) were determined. The treatments used in the INTA Chacharramendi Annex Field (La Pampa) were: Control; Pastar Gold 1 L ha-1; Pastar Gold 2 L ha-1; Sendero 3 L ha-1 and Sendero 4 L ha-1, in a randomized complete block design. The application was in november 2017, with a drag sprayer at 240 L ha-1 of broth. The species studied were affected by application of the treatments (p≤0,05). Mortality was 34 - 41 % in N. flexuosa var. depressa, 29 – 35 % in N. flexuosa, 1 - 4 % in C. microphylla and 16 - 23 % in L. chilense. The herbaceous dicotyledons were damaged by the application of the treatments, however the perennial and annual poaceae did not present phytoxicity. BHAT increased significantly (p≤0,05) at 6 and 12 months (15 - 43 % and 89 - 143 %, depending on treatment, respectively), as did BAPP at 12 months (72 - 124 %) post-application vs. the control. After 18 months BHAT and BAPP did not differ significantly from the control, but they did differ numerically. The herbicide and doses used showed control of the woody species, releasing essential resources that made it possible to increase the area productivity of the herbaceous stratum.